2014
DOI: 10.1111/jeb.12332
|View full text |Cite
|
Sign up to set email alerts
|

When a clonal genome finds its way back to a sexual species: evidence from ongoing but rare introgression in the hybridogenetic water frog complex

Abstract: Besides several exceptions, asexual metazoans are usually viewed as ephemeral sinks for genomes, which become 'frozen' in clonal lineages after their emergence from ancestral sexual species. Here, we investigated whether and at what rate the asexuals are able to introgress their genomes back into the parental sexual population, thus more or less importantly affecting the gene pools of sexual species. We focused on hybridogenetic hybrids of western Palaearctic water frogs (Pelophylax esculentus), which originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 79 publications
(95 reference statements)
2
25
0
Order By: Relevance
“…In contrast, triploid LLR hybrids in the four populations of types 3 and 4 occurred as males only; LLR females were neither caught during this study (Table ) nor found during previous samplings performed by Mikulíček et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, triploid LLR hybrids in the four populations of types 3 and 4 occurred as males only; LLR females were neither caught during this study (Table ) nor found during previous samplings performed by Mikulíček et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, hybridogenesis of water frogs ( Pelophylax esculentus ) has been suggested to be a genetic sink for sexual species. However, a recent study showed evidence that the water frog hybrids were able to mediate mtDNA transfer to its parental species ( P. ridibundus ) (Mikulïček, Kautman, Demovič, & Janko, ). Interestingly with our studying species, Ko () described how triploid hybrid females could transmit genetic material to the parental species by backcrossing (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we might consider the fit of pseudogamous scenarios, as in gynogenetic species (Choleva et al., ), where male stimulation of embryogenesis is necessary in order to catalyze reproductive processes (Schlupp, ). It is hypothesized that this form of asexuality also develops from rare sexual reproduction (Mikulíček, Kautman, Demovič, & Janko, ), and while Tsurusaki disproved the necessity of males for parthenogenesis in L. manubriatum (Tsurusaki, ), the possibility remains for variation in reproductive mode in isolated populations of the species. Such reproductive mechanisms have never been described in Opiliones, but could explain a portion of the discordance between the nuclear and mtDNA data in these species.…”
Section: Discussionmentioning
confidence: 99%